2020
DOI: 10.14218/jcth.2019.00060
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Mortality and Predictors of Acute Kidney Injury in Patients with Cirrhosis: A Systematic Review and Meta-analysis

Abstract: Background and Aims: Acute kidney injury (AKI) is common in patients with cirrhosis but the incidence is heterogeneous among studies. We performed a meta-analysis to describe the incidence of AKI and its impact on patient mortality in patients with cirrhosis. We also evaluated the admission variables predicting development of AKI. Methods: A systematic search of various databases was performed up to November 2018. Meta-analyses were performed using random effects models. Results: Of 18,474 patients with cirrho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 54 publications
6
33
3
Order By: Relevance
“…However, high BUN, high MELDNa, high INR, and ALP were clinical parameters and scores that were independent predictors of AKI. Tariq et al [38] reported MELD, CPS stage C, presence of ascites, and presence of sepsis/septic shock as predictors associated with AKI. Gameiro et al [39] in their study also identified MELDNa and neutrophil-to-lymphocyte ratio as an independent predictive factor of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…However, high BUN, high MELDNa, high INR, and ALP were clinical parameters and scores that were independent predictors of AKI. Tariq et al [38] reported MELD, CPS stage C, presence of ascites, and presence of sepsis/septic shock as predictors associated with AKI. Gameiro et al [39] in their study also identified MELDNa and neutrophil-to-lymphocyte ratio as an independent predictive factor of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis finds that AKI increases the risk of acute coronary syndrome, suggesting that AKI increases the risk of early mortality[ 19 ]. Our study suggests AKI, one of the most common complications of cirrhosis, is one of the highest predictors of mortality in the LC cohort, second only to cardiac arrest[ 1 , 20 ]. This is likely due to the underlying disease-specific physiology of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Tariq et al performed a meta-analysis involving 18,474 patients with cirrhosis and found that the MELD score was related to AKI. 7 In addition, an increased MELD-XI score was validated to be an independent risk factor for AKI in patients with postcardiotomy cardiogenic shock treated with venoarterial extracorporeal membrane oxygenation by another retrospective study. 8 Similarly, in a prospective observational study, 131 patients who underwent hepatobiliary surgeries were analyzed and it was suggested that a higher level of the MELD-Na score was significantly associated with an increased risk of developing AKI.…”
Section: Incremental Effects Of Meld Score and Its 3 Modifications On The Predictive Potential Of Model 3 For Ca-akimentioning
confidence: 99%